TECHNOLOGY FOR EFFICIENT USAGE OF HYDROCARBON-CONTAINING WASTE IN PRODUCTION OF MULTI-COMPONENT SOLID FUEL - B. M. Khroustalev; A. N. Pekhota (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers modern approaches to usage of hydrocarbon-containing waste as energy resources and presents description of investigations, statistic materials, analysis results on formation of hydrocarbon-containing waste in the Republic of Belarus. Main problems pertaining to usage of waste as a fuel and technologies for their application have been given in the paper. The paper describes main results of the investigations and a method for efficient application of viscous hydrocarbon-containing waste as an energy-packed component and a binding material while producing a solid fuel. A technological scheme, a prototype industrial unit which are necessary to realize a method for obtaining multi-component solid fuel are represented in the paper. A paper also provides a model of technological process with efficient sequence of technological operations and parameters of optimum component composition. Main factors exerting significant structure-formation influence in creation of structural composition of multi-component solid fuel have been presented in the paper. The paper gives a graphical representation of the principle for selection of mixture particles of various coarseness to form a solid fuel while using a briquetting method and comprising viscous hydrocarbon-containing waste. A dependence of dimensionless concentration g of emissions into atmosphere during burning of two-component solid fuel has been described in the paper. The paper analyzes an influence of the developed methodology for emission calculation of multi-component solid fuels and reveals a possibility to optimize the component composition in accordance with ecological function and individual peculiar features of fuel-burning equipment. Special features concerning storage and transportation, advantages and disadvantages, comparative characteristics, practical applicability of the developed multi-component solid fuel have been considered and presented in the paper. The paper cites practical results pertaining to usage of hydrocarboncontaining waste for the equipment applied for production of multi-component solid fuel. Data on economic expediency for usage of the multi-component solid fuel with high thermo-technical characteristics in the boiler-houses operating on local solid fuel have been analyzed in the paper. The paper shows a perspective evaluation, applicability and practical significance of the solution of the problem on efficient usage of hydrocarbon-containing waste while producing the multi-component solid fuel.